O desenvolvimento cognitivo em adultos: um estudo de caso com licenciandos de física e química - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Jean Piaget's Genetic Epistemology and Gérard Vergnaud's Conceptual Field Theory constructed as essential theories in science education through their assumptions helping to understand the cognitive processes and concepts needed in teaching-learning, adopted as theoretical references of this work. Based on this, the general objective of this research is based, being “to infer which characteristics of the cognitive development according to the theory of Jean Piaget become more evident in students of the degrees in physics and chemistry at UEPG, regularly enrolled in the 1st or 2nd year, of the courses", and for that, it was listed as a specific objective "To point out the cognitive development of students in Piagetian operative activities". Being of a qualitative nature, the adopted methodology was based on a grouping of methodological designs, being a bibliographic research, case study, ex-post-facto research, and the critical clinical method. As an instrument of data collection, an investigative questionnaire and the following Piagetian operative activities used: i) Volume conservation; ii) Combinatory Operations, and iii) Combination of Colored and Colorless Chemical Bodies. Since an initial data collection was carried out, which included the application of the investigative questionnaire and the application of two Piagetian operative activities (i and ii) inspired by the critical clinical method, after this initial collection, a new data collection performed, following all the protocols of the critical clinical method, and recorded in audio and video, with activities i, ii, and iii applied. With this set of data, it could be inferred that the subjects are in the process of transition from aspects of concrete operative thinking to formal operative thinking, corroborated by aspects evidenced by the Vergnaudian theory. Therefore, there is a dire need for educational actions that consider the student's cognitive aspects. However, besides, that also provides the development of such structures, elevating the subject to his status as a university student, within all the possibilities, this educational and scientific context requires.
Keywords: Epistemologia Genética; Teoria dos Campos Conceituais; Ensino Superior; Genetic Epistemology; Conceptual Field Theory; Higher Education; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA